Analysis Of The Efficiency Of The Application Of Non-Cash Payment System (Cashless) At Pt. Nur Haramain Mulia Tour (Kraksaan Head Office) - Zahida I’tisoma Billah; Chovivatur Rahmah (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The evolution of payment systems from cash to non-cash reflects rapid technological advancements in the corporate and banking sectors. This study evaluates the efficiency of the cashless payment system implementation at PT Nur Haramain Mulia Tour, Kraksaan Office. Efficiency in this research is defined by five key indicators: transaction time savings, administrative cost reduction, error reduction in financial recording, transparency, and service speed. Using a descriptive qualitative approach, this study employed purposive sampling to select participants, including the company’s financial staff, management, and customers. Data were collected through in-depth interviews, field observations, and document analysis, subsequently analyzed using Miles and Huberman’s interactive model (data reduction, display, and conclusion drawing). The results indicate that the implementation of cashless payments at PT Nur Haramain Mulia Tour is currently less efficient as it fails to meet the expected indicators of speed and error reduction. The study identifies four primary barriers: 1) low digital literacy among staff and pilgrims regarding cashless systems, 2) a significant number of clients who do not possess bank accounts, 3) suboptimal data synchronization due to unconfirmed proof of payments, and 4) psychological barriers such as fear of system errors or network failures. Consequently, the non-cash system has not yet provided significant benefits in accelerating transaction flows. This research suggests that the company needs to improve its digital infrastructure and provide literacy programs for users to enhance system efficiency.